2012
DOI: 10.1074/jbc.m112.349944
|View full text |Cite
|
Sign up to set email alerts
|

HIRA, a Conserved Histone Chaperone, Plays an Essential Role in Low-dose Stress Response via Transcriptional Stimulation in Fission Yeast

Abstract: Background: HIRA is a conserved histone chaperone required for regulation of chromatin structure. Results: Genes that encode HIRA proteins are responsible for cross-tolerance. Specifically, stress-responsive gene expression was most profoundly compromised in HIRA disruptants. Conclusion: HIRA is involved in cross-tolerance via regulation of stress-responsive gene expression. Significance: This study provides evidence that fission yeast HIRA functions in stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Considering the genome-wide effect of HIRA on transcription regulation post UVC, it is tempting to speculate that HIRA may also stimulate transcription induction of early UV-responsive genes. Lending support to this idea, the ortholog of HIRA in fission yeast is required for the induction of stress-responsive genes 90 . Future studies will address whether this function of HIRA is conserved in higher eukaryotes.…”
Section: Genome-wide Impact Of Hira On Transcription Restart Post Uvmentioning
confidence: 95%
“…Considering the genome-wide effect of HIRA on transcription regulation post UVC, it is tempting to speculate that HIRA may also stimulate transcription induction of early UV-responsive genes. Lending support to this idea, the ortholog of HIRA in fission yeast is required for the induction of stress-responsive genes 90 . Future studies will address whether this function of HIRA is conserved in higher eukaryotes.…”
Section: Genome-wide Impact Of Hira On Transcription Restart Post Uvmentioning
confidence: 95%
“…In yeast, HIRA histone chaperone has been shown to be involved in transcriptional stimulation in response to osmotic and oxidative stresses (Chujo et al, 2012). Previous studies, including ours (Zhu et al, 2013;Tripathi et al, 2015), have suggested that expression of a few plant histone chaperones is perturbed during biotic and abiotic stress conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Taking clues from some previous studies that have shown genome-wide transcriptional changes attributed to the nucleosome assembly/disassembly activity of histone chaperones (Zhu et al, 2006;Chujo et al, 2012), we hypothesized that manipulating the expression of OsNAPL6 may alter the expression of several genes, many of which might be associated with abiotic stress response. Consistent to our hypothesis, we observed large-scale changes in the rice transcriptome when the expression of OsNAPL6 was manipulated by overexpression or knockdown (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ChIP-seq density profiles followed by co-immunoprecipitation show that multiple subunits of the HUCA complex bind to both the initiating and elongating forms of RNAPII [74]. The importance of the interaction between HUCA and RNAPII is underscored by the fact that in yeast cells depleted of HIRA, RNAPII recruitment is impaired [75]. HIRA binds to both subunits of DSIF [76] which travels throughout the coding region along with RNAPII [77].…”
Section: Interactions Between Huca the 26s Proteasome And Rnapiimentioning
confidence: 99%